A Scathel Weed Parthenium hysterophorus Menacing Natural and Agro Ecosystem in Kanchanpur, Nepal - Joshi, M; Bhat, U.; Bhatt, M.D. (Himalayan Biodiversity, 2017)
Eighty plant species were recorded along with Parthenium hysterophorus from different sites, of which 75 species were recorded from site 1, 73 species from site 2 and 77 species from site 3. On the basis of density and IVI, 14 plant species were recorded as dominant (Density >12) among study sites. Alysicarpus vaginalis (17.3), Casia tora (17.0), Cynodon dactylon (19.7), Cyperus rotundus (13.7), Evolvulus nummularis (32.3), Mecardonia procumbens (20.6), Oxalis corniculata (18.6), Parthenium hysterophorus (396.0) and Zizyphus mauritiana (12.0) at site 1. Cynodon dactylon (14.7), Dactyloctenium aegyptium (13.0), Cyperus rotundus (13.0) and Parthenium hysterophorus (135.3) species at site 2 and Cynodon dactylon (19.0), Cyperus rotundus (29.0), Desmodium triflorum (12.6), Digitaria sanguinalis (17.7), Euphorbia hirta (18.6), Evolvulus nummularis (46.6) and Lathirus athaca (12.6) and Parthenium hysterophorus (303.6) species at site 3. The most common species were Evolvulus nummularis, Cynodon dactylon, Imperata cylindrica, Cannabis sativa, Oxalis corniculata, Ageratum haustorium, Lippia nudiflora, Euphorbia hirta, Portulica olearacea, and Solanum xanthocarpum in all sites. From this survey on different sites of Mahendranagar the result obtained as; the maximum density of Parthenium was recorded 396.67 m-2, 135.3 m-2 and 303.7 m-2 at site 1, 2 and 3, respectively. The sign of higher density of Parthenium at site 1 proves the favorable conditions i.e. sandy dry and gravel soil with high temperature. The species richness decreased on increase of Parthenium density in all study sites. Socio-economic surveys recorded health problems for cattle such as skin allergies, wounds, eye redness, and wounds around the mouth, loss of thirst and loss of appetite. The height of the Parthenium was recorded 196.4±2.96 cm, 176 ±7.50 cm and 96.0±9.31 cm at site 1, 2 and 3, respectively. Similarly, highest leaf area, petiole length and circumference was recorded 263.6±22.26 cm2, 8.16±0.77 cm and 7.72±0.64 cm, respectively at site 1, 2 and 3, respectively.